Antipsychotic Polypharmacy and High-Dose Antipsychotic Regimens in the Residential Italian Forensic Psychiatric Population (REMS) - Mandarelli, Gabriele; Carabellese, Felice; Di Sciascio, Guido; Catanesi, Roberto (Frontiers in Psychology, 2022)
Few data exist regarding treatment with antipsychotics in forensic psychiatric patient populations with high social dangerousness. We performed a secondary analysis of 681 patients treated with at least one antipsychotic, extracted from a one-year observational retrospective study, conducted on 730 patients treated in the Italian REMS (96.4% of the REMS population). We aimed at investigating antipsychotic polypharmacy (prescription of two or more concomitant antipsychotics) and high dose / very high dose antipsychotics, as well as the possible factors associated with such therapeutic regimens. High dose / very high dose antipsychotics were defined as a prescribed daily dose to WHO defined daily dose ratio greater than 1.5 or 3.0, respectively. Binary logistic regression analysis was used in three models to test possible predictors of antipsychotic polypharmacy, high dose antipsychotics and very high dose antipsychotics prescription. Antipsychotic polypharmacy resulted in n = 308 (45.2%) of the patients, n = 346 (50.8%) received high-dose antipsychotics, and n = 96 (14.1%) very high-dose antipsychotics. The multivariate analysis disclosed an association between antipsychotic polypharmacy and male gender (OR 2.75, 95% C.I. 1.34–5.65), LAI antipsychotic prescription (OR 2.62, 95% C.I. 1.84–3.74) and aggressive behavior in REMS (OR 1.63, 95% C.I. 1.13–2.36). High dose antipsychotics were also associated with male gender (OR 2.01, 95% C.I. 1.02–3.95), LAI antipsychotic prescription (OR 2.78, 95% C.I. 1.95–3.97) and aggressive behavior in REMS (OR 1.63, 95% C.I. 1.12–2.36). The use of antipsychotic polypharmacy and high dose antipsychotics is frequent in the REMS population. These results might depend on regulatory and organizational aspects of the REMS system, including variability in structures, lack of a common model of care and lack of stratified therapeutic security.